Pengaruh Media Sosial Terhadap Gaya Berbahasa Bagi Kalangan Remaja - R, Rostina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The language used in social media today is partly indifferent to good and correct language rules, therefore learning good and correct Indonesian according to language rules must be learned from an early age. Language is a communication tool used in everyday life, including in social media, without using language, communication will not run well. Social media today is a place where users can express their expressions and desires, especially among teenagers. Social media is basically the latest development of new internet-based web technologies, which makes it easy for everyone to communicate, participate, share and form a network online, after which they will create their own content from their users.